Sikap Pelaku Pariwisata terhadap Potensi Wisata Syariah di Obyek Wisata Telaga Ngebel Ponorogo - Maulana, Hartomi; Setiyono, Ahmad; Rusli, Lathiefa; Astuti, Rahma Yudi (Journal of Management and Business Review, 2021)
Islamic tourism is based on the consideration that tourism has a very large potential market value and will provide great benefits to the people. Even the halal tourism segment is not only for Muslim tourists but also for non-Muslim tourists. This study examines the attitudes of tourism stakeholders toward the potential for Islamic tourism in Ngebel Lake tourism site, Ponorogo. To achieve the objectives, a qualitative approach is applied in this study. This study uses primary data collected through semi-structured interviews involving around 10 respondents consisting of tourists, business actors in the fields of restaurants, hotels and also policy makers (government). Thematic analysis is used as an analysis technique. The results of the study revealed that in general, respondents showed positive support for the potential for implementing Islamic tourism. The study also found that the readiness of implementing Islamic tourism in Ngebel tourism can be seen from the availability of Muslim-friendly facilities such as halal food, places of worship (musholla / mosque), Qibla direction signs and also Muslim friendly accommodation. In addition, the socialization strategy for Islamic tourism needs to be implemented. The study suggests the need to socialize the importance of the halal certification label, especially on food products in order to provide comfort for tourists who come to Ngebel as result it will have implications for increasing tourists.